Binuclear, tetranuclear and hexadecanuclear thio-oxomolybdenum(v/iv) glycolates with selective adsorptions of gases. Issue 3 (23rd November 2022) - Lin, Rong-Yan; Deng, Lan; An, Dong-Li; Zhou, Zhao-Hui
Abstract : Binuclear, tetranuclear and hexadecanuclear thio-oxomolybdenum(v /iv ) glycolates are constructed successively. Different degrees of protonation in glycolates promote the changes in configurations. Gas adsorptions in 4 show discrepant affinities for O2 and CO2 . Abstract : By adjusting the pH values of the solutions, binuclear, tetranuclear and hexadecanuclear glycolato thio- and oxomolybdenum(v /iv ) complexes [MoV2O2 (μ2 -O)(μ2 -S)(Hglyc)2 (Hpz)2 ]·H2 O (1, H2 glyc = glycolic acid, Hpz = pyrazole), (Hdpa)[MoV2O2 (μ2 -S)2 (Hglyc)(glyc)(H2 O)] (2, dpa = 2, 2′-dipyridylamine), (Hdpa)4 [MoV4O4 (μ3 -O)2 (μ2 -S)2 (glyc)2 (S2 O3 )2 ] (3 ) and Na2 [MoIV4MoV12O12 (μ2 -O)6 (μ2 -OH)2 (μ3 -O)12 (glyc)4 (Hpz)4 (pz)8 ]·28H2 O (4 ) have been obtained successfully. Here the glycolates existed in varying aggregates with different degrees of protonation and deprotonation in 1–4 . The stable formations of 1 and 2 are attributed to strong hydrogen bonds formed between the molecules. In particular, the asymmetric unit in 2 is a tetramer linked by hydrogen bonding [2.574(9) Å] between α-hydroxy and α-alkoxy groups for further construction of unsaturated penta-coordination environments. Moreover, deprotonated glycolates act as bridging ligands to form tetra- and hexadecanuclear compounds 3 and 4, respectively. The smallest unit in 4 exhibits mixed valences of 4+ and 5+ simultaneously, where its gas adsorption experiments manifest that 4 is obviously beneficial for O2 and CO2 compared with no adsorption of N2, CH4 and H2 at different pressures.